Assessment of genetic variability, correlation, and path analysis studies in Bangladeshi local rice (Oryza sativa L.) cultivars - M. Ataur Rahman; Md. Sojiur Rahman; Md. Mim Obaidullah; Pinki Akter; Rashiduzzaman Emran; Md. Rayhan Chowdhury (Vegetos, 2026)

Correction: Phytotoxicity and metal mobility in soils contaminated with mine tailings - Andressa Cristhy Buch; Maria Elizabeth Fernandes Correia; Júlia Carina Niemeyer; Douglas Brian Sims; Eduardo Duarte Marques; Krishna Kumar Yadav; Ahmad J. Obaidullah; Camila Rodrigues e Silva; Emmanoel Vieira da Silva-Filho (Environmental Geochemistry and Health, 2026)

Enhanced estimation of total organic carbon in the longmaxi shale formation using supervised machine learning with lithofacies characterization via K-means clustering - Shaukat Khan; Zhishui Liu; Zhiqiang Lu; Wakeel Hussain; Sohail Ahmed; Muhammad Sajid; Hafiz Hussain Ahmad; Obaidullah; Imdadullah (Carbonates and Evaporites, 2026)

Analysis and socioeconomic determinants of the livestock sector in Afghanistan - Johar Ali; Ome Kalsoom Afridi; Sayed Ajmal Qurishi; Obaidullah Mahak (Tropical Animal Health and Production, 2026)

Phytotoxicity and metal mobility in soils contaminated with mine tailings - Andressa Cristhy Buch; Maria Elizabeth Fernandes Correia; Júlia Carina Niemeyer; Douglas Brian Sims; Eduardo Duarte Marques; Krishna Kumar Yadav; Ahmad J. Obaidullah; Camila Rodrigues e Silva; Emmanoel Vieira da Silva-Filho (Environmental Geochemistry and Health, 2026)
The consumption of vegetables is essential for human health. However, in regions affected by mining activities, this practice may pose serious risks due to potential heavy metal contamination at the soil–plant interface. This study evaluated the phytotoxicity and metal mobility in lettuce cultivated in mine tailing-contaminated soils after the Córrego do Feijão dam failure (Brumadinho, Minas Gerais, Brazil). The increase in soil metal concentrations negatively influenced morphological parameters such as root and shoot length, fresh biomass, germination, chlorophyll content, and the pattern and frequency of stomata on the leaf surface. Translocation factors of Fe, Ni, Mn, Cd, Cu, Pb, and Zn from roots to shoots of lettuce indicated significant risks to human health. In shoots, the concentrations of As, Cd, Pb, and Cu exceeded the maximum permissible limits for human consumption in lettuce and other leafy Asteraceae by up to 407-, 98-, 5,483-, and 28-fold, respectively. These results highlight the urgent need for mitigation, remediation, and protective strategies to safeguard human and animal health in mining regions, particularly where mining, agriculture, and livestock production coexist.

Microbial ecology, functional implications, and associated factors influencing poultry intestinal health - Noor Aminullah; Hikmatullah Langar; Obaidullah Mahaq; Mohammad Naeem Azizi; Ahmadullah Zahir (Veterinary Immunology and Immunopathology, 2026)

Utilization of molasses and vinasse as grinding aids for calcite grinding - Serkan Cayirli; Hasan Serkan Gokcen; Nuri Yuce; Obaidullah Elchi; Ahmet Hakan Benzer (Minerals Engineering, 2026)

Microplastics Occurrence in Earthworm (Lampito mauritii) from the Mettur Dam, Southern India and Contamination Indices: Investigation and Indication - Arunagiri Ragu Prasath; Kandasamy Selvam; Krishna Kumar Yadav; Mosab Kaseem; Chinnappan Sudhakar; Ahmad J. Obaidullah (Water, Air, & Soil Pollution, 2025)

Biohydrogen production through dark fermentation of agricultural waste: Novel strain and feedstock characterisation - Ariadna Vidal; Obaidullah Mohiuddin; Ella Chance; Sergio Serrano-Blanco; Thomas P. Howard; Jose Muñoz-Muñoz; Sharon Velasquez-Orta; Leonardo Rios-Solis (Bioresource Technology, 2025)

Effects of mine tailings on the structure and diversity of microbial communities in riparian soils - Andressa Cristhy Buch; Krishna Kumar Yadav; Douglas B. Sims; Maria Elizabeth Fernandes Correia; Eduardo Duarte Marques; Ahmad J. Obaidullah; Emmanoel Vieira Silva-Filho (Environmental Geochemistry and Health, 2025)

Seismic evaluation and strengthening of an RC building using different retrofit techniques in earthquake-prone region of Pakistan - Obaidullah Khan; Muhammad Faisal Javed; Adeel Zafar; Sanaullah Khan (Innovative Infrastructure Solutions, 2025)

Untargeted UHPLC-Q exactive orbitrap HRMS-based network pharmacology for the discovery of anti-breast cancer compounds from spatholobus littoralis stems fractions and experimental validation - Tedi Rustandi; Muhammad Riko Nugroho; Muhammad Yasir; Kamalia; Elza Julian Eka Putri Nugraha; Muhammad Hafizh Abiyyu Fathin Fawwazi; Senya Puteri Amalia; Abdul Mahmud Yumassik; Farida Hayati; Ahmed Mahal; Ahmad J. Obaidullah (Natural Product Research, 2025)

Global thermal bioclimate indicators: spatial shifts and temporal changes - Mohammed Magdy Hamed; Obaidullah Salehie; Ali Salem Al-Sakkaf; Mohammed Rady; Ahmed Abdiaziz Alasow; Shamsuddin Shahid (Climatic Change, 2025)

Mapping indoor overheating exposure rate at city scale: A data-driven method based on building typologies and surrogate-modelling - Obaidullah Yaqubi; Sihem Guernouti; Auline Rodler; Marjorie Musy (Energy and Buildings, 2025)

Evaluating statistical and machine learning techniques for sugarcane yield forecasting in the tarai region of North India - Anurag Satpathi; Neha Chand; Parul Setiya; Rajeev Ranjan; Ajeet Singh Nain; Dinesh Kumar Vishwakarma; Kashif Saleem; Ahmad J. Obaidullah; Krishna Kumar Yadav; Ozgur Kisi (Computers and Electronics in Agriculture, 2025)

Which soil properties could affect the floristic composition of weed communities in saffron fields - Obaidullah Ghafory; Ghorban Ali Asadi; Mehdi Rastgoo; Mohammad Hassan Rashed Mohassel; Abdollah Mollafilabi (Biologia, 2024)

Systematic appraisals of naturally occurring alkaloids from medicinal plants - Oluwole Solomon Oladeji; Kehinde Abraham Odelade; Ahmed Mahal; Ahmad J. Obaidullah; Rahadian Zainul (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Characterization and prediction of PM2.5 levels in Afghanistan using machine learning techniques - Obaidullah Salehie; Mohamad Hidayat Bin Jamal; Shamsuddin Shahid (Theoretical and Applied Climatology, 2024)

Deciphering morphology patterns of environmental microfibers: Insights into source apportionment - Ruoqun Yan; Jiangpeng Li; Jiawei Li; Yang Liu; Zhe Xu; Xinyu Ge; Xiao Lu; Krishna Kumar Yadav; Ahmad J. Obaidullah; Yuanyuan Tang (Water Research, 2024)

A Gamma-ray spectroscopy approach to evaluate clay mineral composition and depositional environment: A case study from the lower Goru Formation, Southern Indus Basin, Pakistan - Wakeel Hussain; Miao Luo; Muhammad Ali; Harith F. Al-Khafaji; Irshad Hussain; Mazahir Hussain; Salah Alshareef Alkfakey Ahmed; Obaidullah (Journal of Applied Geophysics, 2024)

Projection of future water availability in the Amu Darya Basin - Obaidullah Salehie; Mohamad Hidayat bin Jamal; Tarmizi bin Ismail; Sobri Bin Harun; Shamsuddin Shahid (International Journal of Climatology, 2024)
Water scarcity is a major challenge facing many regions worldwide, especially arid and semi‐arid areas that are increasingly vulnerable to climate change. This study aimed to project water availability in the Amu Darya Basin (ADB) of Central Asia under four Shared Socioeconomic Pathways (SSPs) from the Coupled Model Intercomparison Project Phase Six (CMIP6) during two upcoming periods (2020–2059 and 2060–2099). The study used a robust machine learning approach, namely a Random Forest (RF) model, to simulate Gravity Recovery and Climate Experiment (GRACE) Terrestrial Water Storage (TWS) data from precipitation and maximum and minimum temperatures (Tmax and Tmin). It then incorporated precipitation, Tmax and Tmin from four selected CMIP6 GCMs, into a water storage model to project spatiotemporal changes in water availability across the basin. The study also evaluated the relative impacts of land use and population on TWS. Results indicate an increase in TWS by approximately 4 cm in the basin's eastern, northwestern and southwestern regions in both future periods, while a decrease by approximately −4 cm in the remaining areas. These projections suggest that TWS will decline in densely populated regions and increase in certain intensively cultivated areas. The most pronounced increase in TWS is anticipated in the snow‐covered Tundra climate zone of the basin. This is attributed to the melting of glaciers, which contributes to runoff in the tributaries of the Amu River. The findings highlight the importance of considering climate change and socioeconomic factors when projecting water availability in arid and semi‐arid regions. The projected changes in TWS have important implications for water resources management in the ADB, particularly in densely populated and intensively cultivated areas.

Unraveling the impact of digital transformation on green innovation through microdata and machine learning - Yuangang Han; Zhentao Li; Tianchu Feng; Shilei Qiu; Jin Hu; Krishna Kumar Yadav; Ahmad J. Obaidullah (Journal of Environmental Management, 2024)

Investigation of the usage of waste materials and By-Products as grinding aids in calcite grinding - Serkan CAYIRLI; Hasan Serkan GOKCEN; Nuri YUCE; Obaidullah ELCHI (Minerals Engineering, 2023)

Administration of α-lipoic acid and silymarin attenuates aggression by modulating endocrine, oxidative stress and inflammatory pathways in mice - Adnan Karim; Fareeha Anwar; Uzma Saleem; Saniya Fatima; Tariq Ismail; Ahmad J. Obaidullah; Rana O. Khayat; Moneerah J. Alqahtani; Ifat Alsharif; Haroon Khan; Celia Vargas-De-La-Cruz; Muhammad Ajmal Shah (Metabolic Brain Disease, 2023)

The living infinite: Envisioning futures for transformed human-nature relationships on the high seas - Laura M. Pereira; Guillermo Ortuño Crespo; Diva J. Amon; Renuka Badhe; Salomão Bandeira; Frida Bengtsson; Miranda Boettcher; Gabrielle Carmine; William W.L. Cheung; Bwalya Chibwe; Daniel Dunn; Maria A. Gasalla; et al. (Marine Policy, 2023)

Selection of CMIP6 GCM with projection of climate over the Amu Darya River Basin - Obaidullah Salehie; Mohammed Magdy Hamed; Tarmizi bin Ismail; Tze Huey Tam; Shamsuddin Shahid (Theoretical and Applied Climatology, 2023)

Projection of temperature extremes of Egypt using CMIP6 GCMs under multiple shared socioeconomic pathways - Mohammed Magdy Hamed; Obaidullah Salehie; Mohamed Salem Nashwan; Shamsuddin Shahid (Environmental Science and Pollution Research, 2022)

Projection of Hot and Cold Extremes in the Amu River Basin of Central Asia using GCMs CMIP6 - Obaidullah Salehie; Tarmizi bin Ismail; Mohammed Magdy Hamed; Shamsuddin Shahid; Mohd Khairul Idlan Muhammad (Stochastic Environmental Research and Risk Assessment, 2022)

Selection of the gridded temperature dataset for assessment of thermal bioclimatic environmental changes in Amu Darya River basin - Obaidullah Salehie; Tarmizi bin Ismail; Shamsuddin Shahid; Saad Sh Sammen; Anurag Malik; Xiaojun Wang (Stochastic Environmental Research and Risk Assessment, 2022)

Projection of droughts in Amu river basin for shared socioeconomic pathways CMIP6 - Obaidullah Salehie; Mohammed Magdy Hamed; Tarmizi bin Ismail; Shamsuddin Shahid (Theoretical and Applied Climatology, 2022)

Design, synthesis and molecular docking of new [1,2,4] triazolo[4,3-a]quinoxaline derivatives as anticancer agents targeting VEGFR-2 kinase - Nawaf A. Alsaif; Alaa Elwan; Mohammed M. Alanazi; Ahmad J. Obaidullah; Wael A. Alanazi; Abdullah F. Alasmari; Hussam Albassam; Hazem A. Mahdy; Mohammed S. Taghour (Molecular Diversity, 2022)

Design and Optimization of Novel Taste-Masked Medicated Chocolates of Dextromethorphan with In vitro and In vivo Taste Evaluation - Rahat Fatima Naqvi; Ahmad Khan; Muhammad Farooq Umer; Obaidullah Malik; Nisar Ahmad Shahwani (Journal of Pharmaceutical Innovation, 2022)

Ranking of gridded precipitation datasets by merging compromise programming and global performance index: a case study of the Amu Darya basin - Obaidullah Salehie; Tarmizi Ismail; Shamsuddin Shahid; Kamal Ahmed; S Adarsh; Md Asaduzzaman; Ashraf Dewan (Theoretical and Applied Climatology, 2021)

CASPASE-12 and rheumatoid arthritis in African-Americans - Laura Marshall; Mohammad Obaidullah; Trista Fuchs; Naomi S. Fineberg; Garland Brinkley; Ted R. Mikuls; S. Louis Bridges; Evan Hermel (Immunogenetics, 2014)

Effect of dust load on the leaf attributes of the tree species growing along the roadside - R. K. Chaturvedi; Shikha Prasad; Savita Rana; S. M. Obaidullah; Vijay Pandey; Hema Singh (Environmental Monitoring and Assessment, 2013)

Physical and mechanical properties of bamboo wastage cement bonded board - Atanu Kumar Das; Masum Billha; Md. Iftekhar Shams; Md. Obaidullah Hannan (Journal of the Indian Academy of Wood Science, 2012)